Revisiting Our Contribution: How Interactions with Student Affairs Professionals Shape Cognitive Outcomes During College. Issue 2 (14th March 2020) - Martin, Georgianna L.; Smith, Matthew J.; Takewell, William C.; Miller, Allison
Abstract : Building on prior research during the first year of college, this study explores how students' interactions with student affairs professionals impact their growth on cognitive outcomes for students over four years of college.